Etiologies of Childhood Hearing Impairment in Schools for the Deaf in Mali - Yalcouyé, Abdoulaye; Traoré, Oumou; Taméga, Abdoulaye; Maïga, Alassane B.; Kané, Fousseyni; Oluwole, Oluwafemi G.; Guinto, Cheick Oumar; Kéita, Mohamed; Timbo, Samba Karim; DeKock, Carmen; Landouré, Guida; Wonkam, Ambroise (Frontiers in Pediatrics, 2021)
Objectives: To identify the etiologies of hearing impairment (HI) in schools for deaf students and to use a systematic review to summarize reports on the etiologies and clinical and genetic features of HI in Mali. Methods: We included individuals with HI that started before the age of 15 years old. Patients were carefully evaluated under standard practices, and pure-tone audiometry was performed where possible. We then searched for articles published on HI in the Malian population from the databases’ inception to March 30, 2020. Results: A total of 117 individuals from two schools for the deaf were included, and a male predominance (sex ratio 1.3; 65/52) was noted. HI was prelingual in 82.2% (n = 117), and the median age at diagnosis was 12 years old. The etiologies were environmental in 59.4% (70/117), with meningitis being the leading cause (40%, 20/70), followed by cases with genetic suspicion (29.3%, 21/117). In 11.3% (8/ 117) of patients, no etiology was identified. Among cases with genetic suspicion, three were syndromic, including two cases of Waardenburg syndrome, while 15 individuals had non-syndromic HI. An autosomal recessive inheritance pattern was observed in 83.3% of families (15/18), and consanguinity was reported in 55.5% (10/18) of putative genetic cases. Conclusion: This study concludes that environmental factors are the leading causes of HI in Mali. However, genetic causes should be investigated, particularly in the context of a population with a high consanguinity rate.